2014
DOI: 10.1007/s00204-014-1330-7
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability, bioactivity and impact on health of dietary flavonoids and related compounds: an update

Abstract: There is substantial interest in the role of plant secondary metabolites as protective dietary agents. In particular, the involvement of flavonoids and related compounds has become a major topic in human nutrition research. Evidence from epidemiological and human intervention studies is emerging regarding the protective effects of various (poly)phenol-rich foods against several chronic diseases, including neurodegeneration, cancer and cardiovascular diseases. In recent years, the use of HPLC-MS for the analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
339
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 511 publications
(343 citation statements)
references
References 369 publications
0
339
0
4
Order By: Relevance
“…Unabsorbed anthocyanins reaching the large intestine may be converted to other metabolites by resident colonic bacteria, followed by absorption or excretion in the faeces (42,63,64) . Microbiota can degrade anthocyanins to phenolic acids and aldehydes by splitting the C-ring and modifying the remaining A and B-rings (62) . Some of the main metabolites of microbiota degradation are gallic acid, vanillic acid, homovanilic acid, protocatechuic acid (PCA), syringic acid and 4-hydroxybenzoic acid (55,(65)(66)(67)(68) .…”
Section: Bioavailability Of Anthocyaninsmentioning
confidence: 99%
“…Unabsorbed anthocyanins reaching the large intestine may be converted to other metabolites by resident colonic bacteria, followed by absorption or excretion in the faeces (42,63,64) . Microbiota can degrade anthocyanins to phenolic acids and aldehydes by splitting the C-ring and modifying the remaining A and B-rings (62) . Some of the main metabolites of microbiota degradation are gallic acid, vanillic acid, homovanilic acid, protocatechuic acid (PCA), syringic acid and 4-hydroxybenzoic acid (55,(65)(66)(67)(68) .…”
Section: Bioavailability Of Anthocyaninsmentioning
confidence: 99%
“…White mulberries, which are rich in flavonoids, are also known as an important nutritional source for protecting the immune system (Butt et al 2008). Previous studies had revealed that phenolic compounds having a protective effect in coronary heart disease and some types of cancer are also anti-aging owing to their antioxidant characteristics instrumental in eliminating free radicals (Rodriguez-Mateos et al 2014). Because of its high phytochemical content, the black mulberry fruit has been used in folk medicine from old times against several disorders such as nausea, vomiting, digestive disorders, diabetes, hypertension, coughs, anaemia, arthritis, mouth sores, gingival diseases, fever, and fatigue (Gungor and Sengul 2008).…”
Section: Introductionmentioning
confidence: 99%
“…resveratrol) found in grapes, wine, peanuts. For further details of the structures and occurrence of these compounds readers should consult Rodriguez-Mateos (Rodriguez-Mateos et al, 2014), along with the ever expanding Phenol-Explorer database which includes comprehensive information of the polyphenol content of foods (Neveu et al, 2010).…”
Section: Polyphenols Structure and Occurrencementioning
confidence: 99%